Book review/ Ulasan buku - Ibrahim Abu Bakar, (Institut Islam Hadhari Universiti Kebangsaan Malaysia, 2009)
In relation to the Muslim countries or nations, one of the contemporary politico-economic and strategic issues for the United States of America (USA) is a civil democratic Islam. USA has looked for the partners among the Muslim nations but USA has not found a civil democratic Islam in any of the Muslim nations. For USA, the democratic system in the Muslim nations is different from the democratic system in USA. Some of the Muslim nations have accepted the democratic system like Turkey, Egypt, Malaysia, Pakistan, Iran, Sudan, Iraq, and Indonesia. The importance of the existence of a civil democratic Islam in the Muslim nations to USA and the West is undeniable. “Clearly, the United States, the modern industrialized world, and indeed the international community as a whole would prefer an Islamic world that is compatible with the rest of the system: democratic, economically viable, politically stable, socially progressive, and follows the rules and norms of international conduct.”(p.ix).